FATIGUE LIFE PREDICTION OF THIN PLATE CONSIDERING VIBRATION LOADING - QI XiQuan; WANG YanSong; GUO Hui; LIU NingNing (Jixie qiangdu)
In order to avoid the time-domain signal is too long to be loaded,the stress power spectral density simulation and experimental verification are carried out by using the transfer function theory. The Dirlik’s life prediction method is determined according to the bandwidth coefficient. Combined with the S-N curve,the fatigue life based on power spectral density is predicted.Verify the results of life through the time domain method. The results show that the relative error of Dirlik method’s life and time domain method is small,and the life prediction method is accurate,which can provide references for improving the fatigue life precision of automotive components.